Intellectual property in the information age - Katz, Roberta; Stanford Alumni Association (MIll Valley, CA 94941 : Kantola Productions., 1997)
Katz in this resource outlines how law has responded historically to cultural change and summerizes the current state of this development.
VHS.
Keywords: Intellectual property -- Business; Technology transfer -- Law and legislation